2023
DOI: 10.1007/s10853-023-08815-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of copper slag and stainless steel slag as replacements for blast furnace slag in binary and ternary alkali-activated cements

Abstract: Commonly used alkali activation precursors such as blast furnace slag and fly ash will soon become less available due to resource competition, and may cease to be produced in certain regions. This limitation in future supply is a main driving force for the investigation of alternative precursor sources, such as non-blast furnace slags and non-ferrous slags, to produce alkali-activated binders. The current study investigates the incorporation of copper slag (CS) and stainless steel slag resulting from electric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 85 publications
0
5
0
Order By: Relevance
“…and activators which includes various mine tailing slags, red mud, biomass ashes, construction and demolition waste, calcined clays, and more. [50][51][52][53][54][55][56][57][58][59][60] The valorization of widely available, aluminosilicate-containing mine tailings to make geopolymers is also a rich area of potential research. While utilizing such industrial wastes for useful products is a positive aspect, they also introduce new mineralogical and chemical aspects and compounds that can significantly affect the alkali-activation process.…”
Section: What Are the Barriers?mentioning
confidence: 99%
“…and activators which includes various mine tailing slags, red mud, biomass ashes, construction and demolition waste, calcined clays, and more. [50][51][52][53][54][55][56][57][58][59][60] The valorization of widely available, aluminosilicate-containing mine tailings to make geopolymers is also a rich area of potential research. While utilizing such industrial wastes for useful products is a positive aspect, they also introduce new mineralogical and chemical aspects and compounds that can significantly affect the alkali-activation process.…”
Section: What Are the Barriers?mentioning
confidence: 99%
“…Commonly used alkali activation precursors such as GBFS and FA will be less available due to resource pressures. Supply limitation is an important reason to research alternative precursors [22]. AAMs could consume vast quantities of industrial solid waste such as FA, iron ore tailings, and GBFS [23][24][25] and save up to 14% of the cost of replacing precursors and activators with industrial residues [26], making them one of the most promising green cementitious materials [27,28].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing synergistic effects between GBFS and other types of industrial solid wastes could lead to the production of high-performance, environmentally friendly construction materials [22]. A synergistic effect was exhibited within an alkaline environment between GBFS and red mud; when GBFS was partially replaced by red mud, its mechanical properties were comparable to or better than those samples without added red mud [33].…”
Section: Introductionmentioning
confidence: 99%
“…However, the reactivity of NFMS even with a fully amorphous phase is still lower, compared to commonly used precursors like GGBFS. In a study conducted by Stefanini et al, 24 they substituted GGBFS with NFMS and observed that this substitution slowed down the reaction kinetics. It also resulted in a slight increase in porosity (approximately 2% when fully replaced) and a reduction in compressive strength.…”
Section: Introductionmentioning
confidence: 99%